2004
DOI: 10.1021/ja047241h
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Covariance NMR Spectroscopy

Abstract: A novel NMR scheme is presented that establishes homonuclear spin correlations without requiring direct detection of the spin species. This covariance NMR method is experimentally demonstrated for a mixture of amino acids and for the uniformly 13C-labeled cyclic decapeptide antamanide using a 13C-edited TOCSY experiment. The method opens up new avenues for the experimental analysis of molecules containing insensitive spins encountered in biomolecular NMR and analytical chemistry including metabolomics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
169
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(170 citation statements)
references
References 8 publications
1
169
0
Order By: Relevance
“…The peak assignment was taken from the literature (13,20). The two-dimensional 13 C-13 C proton-driven spin exchange spectra were acquired with a mixing time of 600 ms and covariance-processed (26). A total of 64 complex data points were acquired in the indirect dimension at a spectral width of 190 ppm.…”
Section: Methodsmentioning
confidence: 99%
“…The peak assignment was taken from the literature (13,20). The two-dimensional 13 C-13 C proton-driven spin exchange spectra were acquired with a mixing time of 600 ms and covariance-processed (26). A total of 64 complex data points were acquired in the indirect dimension at a spectral width of 190 ppm.…”
Section: Methodsmentioning
confidence: 99%
“…Indirect covariance spectroscopy is a variant of covariance spectroscopy 8 -10 and was originally introduced for establishing 13 C- 13 11 Blinov et al introduced asymmetrical processing of indirect covariance spectra to eliminate potential artifacts. 12,13 The basic idea behind indirect covariance is the following.…”
Section: Methodsmentioning
confidence: 99%
“…Note that matrix F Ð F T has as its elements the dot products between rows of F and the indirect covariance transform of Eqn (1) has the effect that both frequency axes of spectrum C correspond to the indirect frequency axis ω 1 of spectrum F. 11 Therefore, the spectral resolution of C along both dimensions is determined by the spectral resolution along the indirect (ω 1 ) dimension of F. By contrast, the direct covariance spectrum 8 -10 C direct D F T Ð F 1/2 has its resolution along both dimensions determined by the resolution of F along the direct dimension ω 2 . Figure 1 compares a 2D FT NOESY spectrum of ubiquitin ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that lung tissue from lung cancer patients was identified by increased incorporation of carbon from glucose into a variety of metabolites, including TCA cycle intermediates as well as nucleotides [68]. The advantage of the stable isotope-labeled NMR metabolomic approach in cancer is the chemical library of 13 C-labeled isotopes [69]including 13 C-labeled amino acids (such as glutamine, serine, and glycine [70]), 13 C-labeled acetate, and 31 P-labeled phosphorylcholine [71]-thus allowing the determination of metabolic pathways in cancer related to protein and fatty acid synthesis, nucleic acid synthesis, nucleotide synthesis, TCA cycle, and carbohydrate metabolism. It should be noted that this approach is equally applicable to MS-based approaches.…”
Section: Nmr-based Metabolomic Analysis Of Plasma/serum and Urine In mentioning
confidence: 99%